NASIONALISASI PT INALUM MENURUT UNDANG-UNDANG PENANAMAN MODAL (UNDANG-UNDANG NO. 25 TAHUN 2007) : PRO KONTRA INDONESIA DAN JEPANG - Wuryandari, Utji Sri Wulan (Economic Faculty, Attahiriyah Islamic University, 2016)
Research in the sphere of Foreign Investments would be so remote in Indonesia, this research examines the Japanese joint venture legal entity with Indonesia, PT. Inalum which have a potential asset in supporting the improvement of the people's economy. Furthermore PT Inalum engaged in the aluminum smelting ore in North Sumatera that has a hydroelectric power plant which can generate 600 Megawatts of electricity. In Act number 25 of 2007 on Investment Article 7 declared that the nationalization of foreign investment companies occur with requirements, therefore in this study examines the